Regression analysis of the second jump length on small jumping hill HS105 m at winter Olympic games Beijing 2022 - Vodicar, J.; Jošt, B.; Pustovrh, J. (9th International Congress on Science and Skiing, March 18 - 22, 2023, Saalbach-Hinterglemm, Austria, 2023)
INTRODUCTION: The purpose of the study was to establish the multiple correlation between the length of the jump and the selected variables in the second round of competition for men and women at the smaller Olympic Ski jumping hill HS105 m at the 2022 Winter Olympics in Beijing.